If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 6(x + -12) = 0 Reorder the terms: 12x + 6(-12 + x) = 0 12x + (-12 * 6 + x * 6) = 0 12x + (-72 + 6x) = 0 Reorder the terms: -72 + 12x + 6x = 0 Combine like terms: 12x + 6x = 18x -72 + 18x = 0 Solving -72 + 18x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + 18x = 0 + 72 Combine like terms: -72 + 72 = 0 0 + 18x = 0 + 72 18x = 0 + 72 Combine like terms: 0 + 72 = 72 18x = 72 Divide each side by '18'. x = 4 Simplifying x = 4
| 200m-100m+52525=56100+175m | | 9y+36=-12x | | 6y-18x=90 | | 4-8x-3= | | (y^2-9)(8y^2-8y+8)=0 | | 5/7=4x/92 | | 22-3z=13 | | 28=2/5x | | 4(20x+50)=760 | | 12(t)=-16t^2+12 | | (x-6)=-4(2x-3) | | 20-6s= | | 15(250)+20x=4430 | | 4y+5=y | | 2x-5=30-5x | | 28=3+5x | | 2x(2x)=13x+1 | | 3-(2n-14)+10(n-3)= | | =3x^2+2x-15 | | n*4=45 | | 2x^2-20x=78 | | 264+26s= | | 5x+18=3x+20 | | n+37=52 | | (x-6)=-8x-7 | | 4c^2+1773.8c-151666.67=0 | | n+37+52= | | -2x+3x=3x+2 | | 18.17=3g+3.53 | | 5/4x=-1 | | t/9=7/11 | | 5a+9-(2a-3)=4(a-6)+5a-1 |